Avaliação do sistema de vigilância entomológica da doença de Chagas com participação comunitária em Mambaí e Buritinópolis, Estado de Goiás Assessment of an entomological surveillance system for Chagas disease with community participation in Mambaí and Buritinópolis, State of Goiás - Antonio Carlos Silveira; Dilermando Fazito de Rezende; Ana Maria Nogales; Juan José Cortez-Escalante; Cleudson Castro; Vanize Macêdo (Revista da Sociedade Brasileira de Medicina Tropical, 2009)
A vigilância entomológica da doença de Chagas em Mambaí e Buritinópolis, no Estado de Goiás, Brasil, tem sido mantida com participação da população, notificando a presença de vetores nas habitações. Passado longo tempo após instituídas as ações de controle e tendo-se já certificado a interrupção da transmissão vetorial, buscou-se avaliar o conhecimento e as práticas da população nessa situação. Os resultados apontam progressivo desinteresse pelo tema doença de Chagas, atribuível à redução da magnitude do problema representado pela enfermidade, a pouca participação das escolas na vigilância, à pequena importância dos vetores secundários e nativos e, em conseqüência, às limitadas intervenções dos serviços de controle em resposta às notificações. Propõe-se, que atividades de busca direta por amostragem sejam periodicamente realizadas e maior envolvimento das instituições de ensino. Entomological surveillance of Chagas disease in Mambaí and Buritinópolis, in the State of Goiás, Brazil, has been kept up through the local population's participation, consisting of reporting the presence of vectors inside their homes. A long time has elapsed since instituting these control measures and it has now been certified that vector transmission has been halted. Thus, this study sought to evaluate the population's knowledge and practices in this situation. The results show that there has been progressive indifference towards the topic of "Chagas disease", which can be attributed to the reduction in the magnitude of the problem that this disease represented, little participation in surveillance among schools, low epidemiological importance of secondary and native vectors and, consequently, limited control interventions from health services in response to notifications. It is proposed that direct search activities by means of sampling should be carried out periodically, and that there should be greater involvement among teaching institutions.